miR-148a regulates expression of the transferrin receptor 1 in hepatocellular carcinoma - Babu, Kamesh Rajendra; Muckenthaler, Martina (Scientific reports, 2019)
Transferrin receptor 1 (TFR1) is a transmembrane glycoprotein that allows for transferrin-bound iron uptake in mammalian cells. It is overexpressed in various cancers to satisfy the high iron demand of fast proliferating cells. Here we show that in hepatocellular carcinoma (HCC) TFR1 expression is regulated by miR-148a. Within the TFR1 3′UTR we identified and experimentally validated two evolutionarily conserved miRNA response elements (MREs) for miR-148/152 family members, including miR-148a. Interestingly, analyses of RNA sequencing data from patients with liver hepatocellular carcinoma (LIHC) revealed a significant inverse correlation of TFR1 mRNA levels and miR-148a. In addition, TFR1 mRNA levels were significantly increased in the tumor compared to matched normal healthy tissue, while miR-148a levels are decreased. Functional analysis demonstrated post-transcriptional regulation of TFR1 by miR-148a in HCC cells as well as decreased HCC cell proliferation upon either miR-148a overexpression or TFR1 knockdown. We hypothesize that decreased expression of miR-148a in HCC may elevate transferrin-bound iron uptake, increasing cellular iron levels and cell proliferation.
Gesehen am 16.08.2019